FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT UNDERPRICING SAHAM PADA PERUSAHAAN NON KEUANGAN SAAT MELAKUKAN INITIAL PUBLIC OFFERING (IPO) - Elma Abnaina; Rory Handriano; Indra Saputra (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2025)
Underpricing during an IPO is a mechanism to signal company quality. This study aims to analyze the factors that influence stock underpricing in companies conducting Initial Public Offerings (IPOs) on the Indonesia Stock Exchange in the 2022-2024 period. The research method used is a quantitative method with an explanatory research type. The population is 179 and the sample consists of 94 companies experiencing underpricing, selected through a purposive sampling technique of research on companies conducting Initial Public Offerings on the Indonesia Stock Exchange in 2022-2024. Hypothesis testing in this study uses a multiple linear regression model. The results of this study indicate that ROA, DER, and Firm's Age have a partial effect. ROA, DER, and Firm's Age simultaneously have a significant effect with an F value of 12.330 with a significance value (Sig.) of 0.002 on underpricing.